Towards economic independence; papers on the nationalisation of the copper industry in Zambia - Faber, M. L. O.; Potter, J. G. (Cambridge [Eng.] : University Press, 1971)
This book consists of four papers. It contains analysis of the corporate structure of the companies operating on the Northern Rhodesian copperbelt, The second, an account of how the mineral rights claimed by the British South Africa Company. The third consists of proposal or at least a hypothetical solution
Includes bibliographical references
hza 30/01/2019
Loans
Keywords: Copper industry and trade